Tyrosine kinase inhibitors: friends or foe in treatment of hepatic fibrosis? - Qu, Kai (Oncotarget, 2016)
Aberrant activity of tyrosine kinases has been proved to be associated with multiple diseases including fibrotic diseases. Tyrosine kinases inhibitors (TKIs) might be a novel approach to transform the anti-fibrotic treatment. However, both beneficial and adverse effects are observed by researchers when using these TKIs in either preclinical animal models or patients with hepatic fibrosis. Since hepatotoxicity of TKIs is the leading cause for drug withdrawals thus limits its application in anti-fibrosis, not only efficacy but also safety of TKIs should be paid great concerns. It has been observed in a few studies that TKIs could induce relatively high rate of hepatic biochemical markers elevations and even result in liver failure. Fortunately, several strategies have been adopt to handle with the hepatotoxicity. Accumulating evidences suggest that hepatic stellate cells (HSC) play a pivotal role in hepatic fibrogenesis, so it might be a good option to develop selective TKIs specifically targeting HSCs. The present review will briefly summarize the anti-fibrotic mechanism of TKIs, adverse effects of TKIs as well as the novel developed selective delivery of TKIs.